Mu rhythm desynchronization by tongue thrust observation - Sakihara, Kotoe; Inagaki, Masumi (Frontiers in Human Neuroscience, 2015)
We aimed to investigate the mu rhythm in the sensorimotor area during tongue thrust observation and to obtain an answer to the question as to how subtle non-verbal orofacial movement observation activates the sensorimotor area. Ten healthy volunteers performed finger tap execution, tongue thrust execution, and tongue thrust observation. The electroencephalogram (EEG) was recorded from 128 electrodes placed on the scalp, and regions of interest were set at sensorimotor areas. The event-related desynchronization (ERD) and event-related synchronization (ERS) for the mu rhythm (8–13 Hz) and beta (13−25 Hz) bands were measured. Tongue thrust observation induced mu rhythm ERD, and the ERD was detected at the left hemisphere regardless whether the observed tongue thrust was toward the left or right. Mu rhythm ERD was also recorded during tongue thrust execution. However, temporal analysis revealed that the ERD associated with tongue thrust observation preceded that associated with execution by approximately 2 s. Tongue thrust observation induces mu rhythm ERD in sensorimotor cortex with left hemispheric dominance.